Congenital leptin deficiency and leptin gene missense mutation found in two colombian sisters with severe obesity (2019)
Background: Congenital leptin deficiency is a recessive genetic disorder associated with severe early-onset obesity. It is caused by mutations in the leptin (LEP) gene, which encodes the protein product leptin. These mutations may cause nonsense-mediated mRNA decay, defective secretion or the phenomenon of biologically inactive leptin, but typically lead to an absence of circulating leptin, resulting in a rare type of monogenic extreme obesity with intense hyperphagia, and serious metabolic abnormalities. Methods: We present two severely obese sisters from Colombia, members of the same lineal consanguinity. Their serum leptin was measured by MicroELISA. DNA sequencing was performed on MiSeq equipment (Illumina) of a next-generation sequencing (NGS) panel involving genes related to severe obesity, including LEP. Results: Direct sequencing of the coding region of LEP gene in the sisters revealed a novel homozygous missense mutation in exon 3 [NM_002303.3], C350G>T [p.C117F]. Detailed information and clinical measurements of these sisters were also collected. Their serum leptin levels were undetectable despite their markedly elevated fat mass. Conclusions: The mutation of LEP, absence of detectable leptin, and the severe obesity found in these sisters provide the first evidence of monogenic leptin deficiency reported in the continents of North and South America. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.